On the Branch and Cut Method for Multidimentional Mixed Integer Knapsack Problem - Khorramizadeh, Mostafa; Rakhshandehroo, Zahra (International Journal of Applied Mathematical Research, 2014)
In this paper, we examine the effect of the feasibility pump (FP) method on the branch and cut method for solving the multidimentional mixed integer knapsack problem. The feasibility pump is a heuristic method, trying to compute a feasible solution for mixed integer pro- gramming problems. Moreover, we consider two efficient strategies for using the feasibility pump in a branch and cut method and present some tables of numerical results, concerning the application and comparison of using these strategies in the branch and cut method for solving the multidimentional mixed integer knapsack problem. The numerical re- sults indicate that for the majority of the test problems, by using the FP or the imroved version of the FP we can improve the efficiency of the branch and cut method for solving the multidimentional mixed integer knapsack problem. Keywords: Feasibility pump method, Branch and cut method, multidimentional mixed integer knapsack problem.